Outcomes of 1- Versus 2-Stage Revision Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis. Issue 3 (March 2021) - Colatruglio, Matthew; Flanigan, David C.; Long, Joseph; DiBartola, Alex C.; Magnussen, Robert A.
Background: Anterior cruciate ligament reconstruction (ACLR) is a common orthopaedic sports medicine procedure, but graft failure is not uncommon and often leads to revision ACLR. Revision surgery can be performed in a 1- or 2-stage fashion. Hypothesis: Graft failure risk, patient-reported outcomes, and anterior knee laxity are similar after 1- and 2-stage revision ACLR. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review of the literature was performed to evaluate patient outcomes after 1- versus 2-stage revision ACLR. A search was performed with the phrase "revision anterior cruciate ligament reconstruction" across Embase, PubMed, Scopus, and SportDiscus from the beginning of their archives through July 12, 2019. Results: Thirteen studies met inclusion criteria and included 524 patients: 319 patients who underwent 1-stage revision ACLR and 205 patients who underwent 2-stage revision ACLR. Two studies compared outcomes of 1- versus 2-stage revision ACLR; 4 studies reported outcomes after 2-stage revision ACLR; and the remaining 7 studies documented outcomes after 1-stage ACLR. The mean follow-up was 4.1 years. The 2 studies that compared 1- versus 2-stage ACLR reported no differences in functional, radiologic, or patient-reported outcomes or failure risk. Overall, 9 studies reported subjective International Knee Documentation Committee (IKDC) scores; 4 studies, Knee injury and Osteoarthritis Outcome Score values; 8 studies, Lysholm scores; and 7 studies, Tegner scores; 8 studies measured anterior laxity with a KT-1000 arthrometer. The mean weighted subjective IKDC score for all studies including this outcome at final follow-up was 66.6 for 1-stage revisions and 65.9 for 2-stage revisions. Conclusion: The available evidence comparing 1- versus 2-stage revision ACLR is retrospective and limited. The results of each approach are similar in appropriately selected patients.